2012
DOI: 10.4244/eijv8i7a126
|View full text |Cite
|
Sign up to set email alerts
|

Renal tolerability of iopromide and iodixanol in 562 renally impaired patients undergoing cardiac catheterisation: the DIRECT study

Abstract: With rigorous hydration, the CIN incidence was very low in patients with moderate renal dysfunction who underwent coronary angiography or PCI. No difference in nephrotoxicity was found between iopromide and iodixanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Pugh et al (1993) compared iopromide and iodixanol for femoral arteriography; according to McCullough et al (2006a, b) they found a lower rate of CIN after iopromide than after iodixanol. Chen et al (2012) did not find any difference in nephrotoxicity between iopromide and iodixanol in patients undergoing coronary angiography who had moderately reduced renal dysfunction. These conflicting results are typical of this topic.…”
Section: Non-ionic Contrast Mediamentioning
confidence: 87%
“…Pugh et al (1993) compared iopromide and iodixanol for femoral arteriography; according to McCullough et al (2006a, b) they found a lower rate of CIN after iopromide than after iodixanol. Chen et al (2012) did not find any difference in nephrotoxicity between iopromide and iodixanol in patients undergoing coronary angiography who had moderately reduced renal dysfunction. These conflicting results are typical of this topic.…”
Section: Non-ionic Contrast Mediamentioning
confidence: 87%
“…In this study, we named, i.e. Chen (1) 2012 that meant Chen 2012 [ 19 ] with the data of relative CIN criterion, while the Chen (2) 2012 meant the absolute criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the change of absolute or relative SCr concentration remains a key parameter in the diagnosis of CIN. Intravenous saline hydration and the use of low-osmolality contrast medium has been accepted as preventive strategies for CIN (4951). …”
Section: Discussionmentioning
confidence: 99%